Quantitative elemental mapping of granulite-facies monazite: Textural insights and implications for petrochronology - Weller, OM; Jackson, S; Miller, WGR; St-Onge, MR; Rayner, N (Wiley, 2020)
Abstract Texturally complex monazite grains contained in two granulite‐facies pelitic migmatites from southern Baffin Island, Arctic Canada, were mapped by laser ablation‐inductively coupled plasma‐mass spectrometry (using spot sizes ≤5 µm) to quantitatively determine the spatial variation in trace element chemistry (with up to 1,883 analyses per grain). The maps highlight the chemical complexity of monazite grains that have experienced multiple episodes of growth, resorption and chemical modification by dissolution–precipitation during high‐grade metamorphism. Following detailed chemical characterization of monazite compositional zones, a related U–Pb data set is re‐interpreted, allowing petrologically significant ages to be extracted from a continuum of concordant data. Synthesis of these data with pseudosection modelling of prograde and peak conditions allows for the temporal evolution of monazite trace element chemistry to be placed in the context of the evolving P – T conditions and major phase assemblage. This approach enables a critical evaluation of three commonly used petrochronological indicators: linking Y to garnet abundance, the Eu anomaly to feldspar content and Th/U to anatectic processes. Europium anomalies and Th/U behave in a relatively systematic fashion, suggesting that they are reliable petrochronological witnesses. However, Y systematics are variable, both within domains interpreted to have grown in a single event, between grains interpreted to be part of the same age population, and between samples that experienced similar metamorphic conditions and mineral assemblages. These observations caution against generalized petrological interpretations on the basis of Y content, as it suggests Y concentrations in monazite are controlled by domainal equilibria. The results reveal a c . 45 Myr interval between prograde metamorphism and ...